A novel approach for scrapie-associated prion (PrPSc) detection in blood using the competitive affinity of an aggregate-specific antibody and streptavidin to PrPSc. (August 2017) - Soutyrine, Andrei; Huang, Hongsheng; Andrievskaia, Olga; Walther, Ines; Mitchell, Gordon
Abstract: Scrapie is a fatal neurodegenerative disorder affecting sheep and goats, originating from exposure to disease-associated prions (PrP Sc ). An ante-mortem screening test that can detect native PrP Sc in body fluids remains unavailable due to insufficient sensitivity of current detection methods that involve proteinase or denaturation treatments. We adopted an approach to detect PrP Sc in whole blood using a simple proteinase- and denaturation-independent immunoassay, based on the competitive affinity of an aggregate-specific monoclonal antibody and streptavidin to PrP Sc . First, we demonstrated the ability of native PrP Sc to bind to streptavidin and the inhibition of this interaction by 15B3 antibody (P < 0.05). This led to a new two-step assay that involved capturing native prions from infected blood on a solid-state matrix and detection of PrP Sc aggregates by evaluating the conformation-dependent conjugate catalytic activity ratio in samples against a pre-determined threshold. This test showed capacity for detecting scrapie prions in 500 μl of sheep whole blood spiked with scrapie brain homogenate containing approximately 5 ng of total brain protein, and estimated to have 500 fg of PrP Sc . The test also discriminated between blood samples from scrapie-negative (6 sheep, 4 goats) and scrapie-infected animals (3 experimentally infected sheep, 7 naturally infected goats). Collectively, with the proposed high-throughput sample-processing platform, these initial studies provide insights into the development of a large-scale screening test for the routine diagnosis of scrapie. Highlights: A novel approach exploited to develop an assay for PrP Sc in blood of small ruminants. Assay does not require protease treatment or denaturation. Method is based on competitive affinity of an antibody 15B3 and streptavidin to PrP Sc . Assay discriminated between blood samples from scrapie negative and infected animals.